2022
DOI: 10.1002/biof.1879
|View full text |Cite
|
Sign up to set email alerts
|

α‐Asarone alleviates allergic asthma by stabilizing mast cells through inhibition of ERK/JAK2‐STAT3 pathway

Abstract: Asthma is a heterogeneous disease related to numerous inflammatory cells, among which mast cells play an important role in the early stages of asthma. Therefore, treatment of asthma targeting mast cells is of great research value. α‐Asarone is an important anti‐inflammatory component of the traditional Chinese medicine Acorus calamus L, which has a variety of medicinal values. To investigate whether α‐asarone can alleviate asthma symptoms and its mechanism. In this study, we investigated the effect of α‐asaron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…In addition, Evans blue exudation images on paws showed a consistent trend with dorsal skin tissue (Figure d,g). Typically, a certain degree of inflammatory reaction will happen along with allergic stimulation, which can induce the thickness of paws to increase . By measuring the thickness changes of paws before and after treatment, as shown in Figure f, the swelling of paws was reduced after the nanocarriers group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Evans blue exudation images on paws showed a consistent trend with dorsal skin tissue (Figure d,g). Typically, a certain degree of inflammatory reaction will happen along with allergic stimulation, which can induce the thickness of paws to increase . By measuring the thickness changes of paws before and after treatment, as shown in Figure f, the swelling of paws was reduced after the nanocarriers group.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, a certain degree of inflammatory reaction will happen along with allergic stimulation, which can induce the thickness of paws to increase. 66 By measuring the thickness changes of paws before and after treatment, as shown in Figure 4f, the swelling of paws was reduced after the nanocarriers group. The thickness of the paws almost returned to a normal level after the treatment of Se MSNs@CS@Ap.…”
Section: Sementioning
confidence: 97%
“…Up to now, several studies have shown that it promotes the symptoms of asthma. Jak2 mRNA and p‐JAK2 protein significantly increase following OVA or PM2.5 exposure to induce airway inflammation 65,85 . Shen et al 86 confirmed that airway smooth muscle cells (ASMCs) migration and proliferation are controlled by Jak2 in the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Jak2 mRNA and p-JAK2 protein significantly increase following OVA or PM2.5 exposure to induce airway inflammation. 65,85 Shen et al 86 confirmed that airway smooth muscle cells (ASMCs) migration and proliferation are controlled by Jak2 in the pathogenesis of asthma. Recent studies have shown that the JAK2 signaling pathway has been demonstrated to be a keystone of M1 macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation